Superbugs online: co-production of an educational website to increase public understanding of the microbial world in, on, and around us - Tyrrell, Jon M.; Hatch, Sarah; Flanagan, Melissa; Owen, Kerry; Proctor, Yvonne; Stone, Catherine; Fricker, Geoff; Hullis, Kirk; Eberl, Matthias (Frontiers in Microbiology, 2024)
Digital tools and online presence have become a cornerstone to public engagement and involvement strategy and delivery. We here describe the co-production process behind launching a new multilingual resource for schools in the UK and beyond, jointly between university scientists, engagement professionals, primary and secondary teachers, and web designers. The ‘Superbugs’ website aims at raising awareness and increasing public understanding of the microbial world in, on and around us – with a focus on infection, hygiene and antimicrobial resistance – and attracted >19,000 online visitors, >33,500 page views and >775,000 Twitter impressions over the past 24 months. Superbugs.online is available in English, Welsh, Irish and Scottish Gaelic, thus making it accessible to everyone in the UK and Ireland, regardless of the language in which they receive and deliver their science education. The website is easy to navigate and features background information, quizzes, animations, videos, illustrated stories, interactive timelines, games and protocols for home experiments. All materials are presented in a non-prescriptive way, aimed at allowing flexibility for the materials to be adapted to the individual needs of teachers and pupils alike. Our work has led to demonstrable impact on the co-production team and on pupils and teachers as key stakeholders, based on a comprehensive evaluation of the co-production process itself, the impact of the end product, and the creation of lasting relationships with stakeholders and co-producers, for the mutual benefit of everyone involved.